Exploring Teacher Traits in Classroom Practices - Neupane, Nabaraj (Janapriya Journal of Interdisciplinary Studies, 2019)
Teachers play a key role to proliferate the educational system as they are at the implementation level of educational acts, rules and regulations. Their traits are at a flux because of temporal and contextual variations encountered in different settings. This context led this study to explore teacher traits in real classroom practices. To achieve this goal, phenomenological research design, as a type of qualitative inquiry, has been adopted. The population of the study comprised the stakeholders of Bachelor of Mountain Tourism Management (BMTM) programme conducted in Janapriya Multiple Campus, Pokhara. The tool for collecting information was non-participant class observation, in which three classes were observed. The results of the study reveal that teacher traits can be measured by triad roles like professional, administrative, and social dimensions. The study implies that teachers should be aware of these triad roles; and the current pedagogical trends and practices.